Experimental study on strength degradation and meso-structural characteristics of saturated sandstone under freeze-thaw cycles - Haotian XIE; Ying XU; Qiangqiang ZHENG; Meilu YU; Shoudong XIE; Chengjie LI (Meitan kexue jishu)
Freeze-thaw damage to rock masses on slopes constitutes a major hazard in open-pit mining operations, particularly in the cold regions of the western area. In order to investigate the mechanical properties and microstructural degradation patterns of slope rocks subjected to freeze-thaw cycles, this study conducted static compression tests on fully saturated sandstone specimens exposed to varying numbers of freeze-thaw cycles (0、20、40、60、80 cycles). Moreover, nuclear magnetic resonance and scanning electron microscopy techniques were employed to examine changes in internal pores and morphologies of the saturated sandstone before and after freeze-thaw, analyze the evolution patterns of porosity, microstructure characteristics, and static compression strength of saturated sandstone under freeze-thaw conditions and establish a predictive model for the strength degradation of saturated sandstone over freeze-thaw cycles. The results reveal the following: With the increased freeze-thaw cycles, the elastic modulus of saturated sandstone exhibits a linear decrease. After 80 cycles of freeze-thaw, the static compressive strength sees a decrease of 28.13%. Moreover, a negative correlation is found between static compressive strength and porosity. Freeze-thaw action gives rise to the detachment and precipitation of weaker mineral particles within the rock sample and induces an obvious weakening effect on its microstructure. This damage to the microstructure further exacerbates its macroscopic mechanical properties. Influenced by freeze-thaw cycles, the pore size distribution of saturated sandstone exhibits a “triple-peak” pattern. With increased freeze-thaw cycles, small pores undergo expansion, which causes the development of intermediate and large pores. The area of the nuclear magnetic resonance T2 spectrum increases, along with a corresponding rise in the proportion of intermediate and large pores. The predictive model for the strength degradation of saturated sandstone under freeze-thaw conditions follows an exponential equation. This model provides meaningful decay constants and half-life parameters for the mechanical performance and durability of rock under freeze-thaw action. The well-suited fitting between the change in porosity and the relative peak strength effectively reflects the degradation pattern of saturated sandstone under varying numbers of freeze-thaw cycles.